Synergistic effects of ascorbic acid, low methoxy pectin, and EDTA on stabilizing the natural red colors in acidified beverages - Qi Guo (Elsevier, 2021)
Betacyanins are one of the reddish to violet betalain pigments that are unstable under an oxygen atmosphere, greatly limiting their application and commercial potential. To improve the betacyanins color stability, we explored synergistic effects between ascorbic acid (AA), polysaccharides, and Ethylenediaminetetraacetic acid (EDTA) to improve the color stability of betacyanins in acidified conditions. We found that alginate and low methoxy pectin (LMP), among the thirteen studied polysaccharides, increased the red color stability of beetroot extract at pH 3.2 during thermal treatment. Our results proved that there is a synergistic effect between polysaccharides, AA, and EDTA, for enhancing the betacyanins color stability. Further, the red color in a model sports beverage recipe protected by the LMP, AA, and EDTA was stable for up to 45 days at room temperature and under natural light. The synergistic stabilization of betacyanins in acidified beverages was confirmed through ATR-FTIR and quartz crystal microbalance with dissipation analyses.